Regional Development Performance of Nduga Regency - Purwadi, Marsi Adi; Fabian, Aquarisal Patrick; Bisai, Charley M.; Klara, Antonia; Kreuta, Balthazar (International Journal of Science and Society, 2024)
This study aims to identify the progress of macro indicators of regional development as well as strategic development issues in Nduga Regency. The background of this research is based on the importance of measuring regional development in a multidimensional manner to understand inequality and to guide more accurate policy directions. The results show that macro indicators such as GRDP per capita, the Human Development Index (HDI), and the electrification ratio have shown an increasing trend. However, major challenges remain in terms of equitable access to education, healthcare, and poverty alleviation. In addition, strategic issues identified include demographic bonus, labor market disparities, limited infrastructure, technological disruption, and regional economic transformation. These findings highlight the need for data-driven, cross-sectoral, and inclusive development strategies to promote sustainable growth and improve the well-being of communities in Nduga Regency.